Kingdom of Lesotho : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that since 2010, the Lesotho's economy has performed well with the growth of real GDP averaging over 5 percent a year and inflation held to single-digit levels. International reserves have recovered to close to 5 months of import coverage after dipping to 3 1\2 months of imports in 2012 in the wake of the balance of payments and fiscal crisis. The economic outlook for Lesotho is positive with strong economic growth and low inflation. Economic activity is expected to be supported by large public investment projects, including the second phase of Lesotho Highland Water Project.